Economic Growth, Markets and the Rule of Law: Brief Considerations on the Brazilian Case - Alexandre B. Cunha (BBR: Brazilian Business Review)
The existence of markets that operate smoothly is an important factor influencing a nation’s economic growth. Furthermore, an effective judicial system is a necessary condition for markets to function well. Therefore, it is reasonable to expect a positive relationship to exist between income per capita and adhesion to the rule of law. This conjecture is corroborated here in a sample of 110 countries in 2016. Additionally, the data show that the rule of law is relatively weak in Brazil, suggesting that an improvement of the Brazilian judicial system is a potential growth-enhancing reform.